Insecticide Seed Treatments Reduced Crop Injury from Flumioxazin, Chlorsulfuron, Saflufenacil, Pyroxasulfone, and Flumioxazin + Pyroxasulfone + Chlorimuron in Soybean - N. R. Steppig; J. K. Norsworthy; R. C. Scott; G. M. Lorenz (International Journal of Agronomy)
With increased instances of weed resistance to applications of postemergence herbicides, the use of soil-applied herbicides that offer residual activity is becoming popular. Unfortunately, under some conditions, the use of residual herbicides can result in unintentional injury to crops. However, there are a number of ways to reduce these risks, including the use of in-crop herbicide safeners. Based on previous research conducted on rice, the potential may exist for crop injury from certain soil-applied herbicides to be reduced (safened) in seeds treated with insecticides. Field trials were conducted in Marianna, Arkansas, in 2015 and 2016, and near Colt, Arkansas, in 2016, to explore this possibility in soybean. Soybean seeds were treated with the insecticide thiamethoxam and subsequently the herbicides metribuzin, saflufenacil, pyroxasulfone, sulfentrazone, chlorimuron, flumioxazin, flumioxazin + pyroxasulfone + chlorimuron, mesotrione, and chlorsulfuron were applied immediately after planting. Of the nine herbicides evaluated, the insecticide reduced crop injury for flumioxazin, chlorsulfuron, saflufenacil, pyroxasulfone, and flumioxazin + pyroxasulfone + chlorimuron. The highest degree of injury reduction was seen 1 week after emergence (WAE) at Marianna, where injury from flumioxazin + pyroxasulfone + chlorimuron was reduced from 15% to 5%. Based on the results from this study, the insecticide seed treatment thiamethoxam may have the potential to safen soybean to applications of some soil-applied herbicides.